2022
DOI: 10.25177/jfst.7.2.ra.10810
|View full text |Cite
|
Sign up to set email alerts
|

Indian blackberry (Syzigium cumini L.) nectar processed without chemical preservatives-changes in physico-chemical properties and bioactive constituents during storage-siftdesk

Abstract: Indian blackberry fruit is widely acclaimed for the antidiabetic property. The fruits are highly perishable, having a shelf life of about two days. Therefore, an attempt was made to convert the fruits into nectar by pasteurization, without adding any chemical preservatives. Indian blackberry nectar having a total soluble solids content of 17 0 Brix and acidity of 0.253% without any chemical preservatives, was pasteurized at 100 0 C, for 10 minutes. Viscosity of the nectar recorded an upward trend throughout st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
6
4
0
Order By: Relevance
“…Decline in TSS content of the product may be due to fermentation process during which sugars are broken down into ethanol, carbon dioxide and water, along with production of volatile compounds. This finding is in agreement with those reported by Saji Gomez et al ( 2022 ) wherein a drop in TSS was recorded in Indian blackberry nectar during storage. Kaddumukasa et al ( 2017 ) also reported decline in 0 Brix values in fresh unpasteurized juice of fruits like mango, pineapple and passion fruit during a storage period of 12 days under ambient and refrigerated conditions.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Decline in TSS content of the product may be due to fermentation process during which sugars are broken down into ethanol, carbon dioxide and water, along with production of volatile compounds. This finding is in agreement with those reported by Saji Gomez et al ( 2022 ) wherein a drop in TSS was recorded in Indian blackberry nectar during storage. Kaddumukasa et al ( 2017 ) also reported decline in 0 Brix values in fresh unpasteurized juice of fruits like mango, pineapple and passion fruit during a storage period of 12 days under ambient and refrigerated conditions.…”
Section: Resultssupporting
confidence: 94%
“…Thakur et al ( 2018 ) also reported that the ascorbic acid content of wild Indian gooseberry fruit syrup declined during storage. The results are in accordance with those already reported by Hosseini et al ( 2015 ) in orange nectar prepared with steviol glycosides and also the decline of ascorbic acid in Indian blackberry nectar during storage by Gomez et al ( 2022 ). Chia et al ( 2012 ) reported that the presence of dissolved oxygen in fruit juices could lead to its degradation during long-term storage.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Tis indicated that jamun fruit followed the acidic foods. Similar fndings were reported for pH (3.0-3.77), titratable acidity (0.8-5.25%), and TSS (8-19.36 °Brix) of jamun fruits [3,13,41,42].…”
Section: Physiochemical Propertiessupporting
confidence: 81%
“…It is one of the underutilized crops because there is no organized farming [2]. It is an extremely perishable fruit having a very short shelf life of 1-2 days under ambient conditions [3]. Ancient medicine made extensive use of jamun fruits to treat a wide range of illnesses and physiological disorders [4].…”
Section: Introductionmentioning
confidence: 99%